The Knowledge and The Hydration Status of Junior Martial Art Athletes - Tirtasari, Ajeng Sindi; Ashadi, Kunjung (UNIVERSITAS NEGERI MAKASSAR, 2021)
The purpose of this study was to determine the adequacy of fluids in the body during training for youth athletes of martial arts. The research method uses descriptive quantitative. Data collection techniques were obtained from urine tests, interviews, and multiple choice questions on 10 athletes consisting of five male athletes and five female athletes of martial art with a maximum age criteria of 18 years. Data analysis techniques used mean, standard deviation, percentage, graph, normality, and different test Paired Sample T Test to find out the difference in the mean. Athletes' knowledge of hydration was in the moderate category and there was a significant difference (Sig. <0.05) in the average hydration before and after training by the Madiun Regency martial art athletes. Â